Pedagogical Opportunities of Using Artificial Intelligence to Improve the Quality of Higher Education - Murodova Rano Buronovna (Researchparks Publishing, 2026)
This article provides a scientific analysis of the application of artificial intelligence technologies in higher education and their impact on educational quality. It highlights the pedagogical potential of artificial intelligence, particularly the significance of adaptive learning, personalized approaches, and automated assessment systems. The study also examines the role of AI-based platforms in effectively organizing the learning process, assessing students’ knowledge, and fostering their independent learning skills. Furthermore, it demonstrates the potential of these technologies to optimize teachers’ work, ensure the continuity of the educational process, and promote equity in education, while also analyzing the technical, organizational, and ethical challenges associated with the implementation of artificial intelligence.